ECONOMIC AND SOCIAL PROCESSES IN EDUCATION: DEVELOPMENT OF UNIVERSITIES IN THE CONTEXT OF INTERNATIONAL TRENDS - Yurievich Viktorov, Viacheslav; Vladimirovna Luneva, Elena; ergeevna Malysheva, Olga; Nicolaevna Pogodina, Olga (Revista Inclusiones, 2020)
In the 21st century, the role of universities as centers of knowledge in ensuring the competitiveness of national economies grows in connection with the strengthening of globalization processes in various spheres of human activities and the transition of developed countries to the postindustrial society model. Information becomes a strategic resource while the generation of new knowledge, creation of innovations, and their rapid commercialization provide competitive advantages and stimulate further economic development. At the same time, there is a tendency towards the internationalization of higher education and the demand for the results of the intellectual activity of universities becomes global.